Educational values and challenges of i-STEM project-based learning: A mixed-methods study with data-transformation design - Chang, Chi-Cheng; Chen, Yi-Kai (Frontiers in Psychology, 2022)
Integrated STEM embedding project-based learning (i-STEM PjBL) is still faced with challenges and its educational values have not revealed that are what the study aimed to explore. Participants consisted of 48 freshmen of a senior high school, including 27 males and 21 females. The open-ended questionnaire and the interview for students were administrated after the i-STEM PjBL. The qualitative data was converted into quantitative data counted by the occurrence frequencies of the codes. The results based on the integration and comparison of the open-ended questionnaire and interview outcomes showed that i-STEM PjBL provided students with positive educational values (including learning acquisition, performance and perception), but there were also learning challenges in the process. Learning acquisition focused on the basic structure and components of robot, principles of robot motion, hull structure, principles of sailboat navigation, skills of designing and assembling sailboats. Learning performance referred that students were satisfied with their hands-on performances, confident of their abilities to perform better in similar disciplines, and they did not learn well on programming. Learning perception included students felt interested in i-STEM PjBL materials, they could acquire knowledge and skills from various fields, PjBL was helpful to complete works and principles were helpful in practice, while programming design learning materials were not enough. Learning challenges included that students were unfamiliar with the usage of tools and hands-on operation, and they also felt challenged by programming. Students’ feedback can be taken as references to modify and improve i-STEM PjBL and the materials in the future.